Changing Contributions of Different Agricultural Policy Instruments to Global Reductions in Trade and Welfare - Croser, Johanna; Anderson, Kym (2012)
Trade negotiators and policy advisors are keen to know the relative contribution of different farm policy instruments to international trade and economic welfare. Nominal rates of assistance or producer support estimates are incomplete indicators, especially when (especially in developing countries) some commodities are taxed and others are subsidized, in which case positive contributions can offset negative contributions. This paper develops and estimates a new set of more-satisfactory indicators to examine the relative contribution of different farm policy instruments to reductions in agricultural trade and welfare, drawing on recent literature on trade restrictiveness indexes and a recently compiled database on distortions to agricultural prices for 75 developing and high-income countries over the period 1960 to 2004. Results confirm earlier findings that border taxes are the dominant instrument affecting global trade and welfare, but they also suggest declines in export taxes contributed nearly as much as cuts in import protection to global welfare gains from agricultural policy reforms since the 1980s.